2013
DOI: 10.1038/cdd.2013.137
|View full text |Cite
|
Sign up to set email alerts
|

Proline oxidase–adipose triglyceride lipase pathway restrains adipose cell death and tissue inflammation

Abstract: The nutrient-sensing lipolytic enzyme adipose triglyceride lipase (ATGL) has a key role in adipose tissue function, and alterations in its activity have been implicated in many age-related metabolic disorders. In adipose tissue reduced blood vessel density is related to hypoxia state, cell death and inflammation. Here we demonstrate that adipocytes of poorly vascularized enlarged visceral adipose tissue (i.e. adipose tissue of old mice) suffer from limited nutrient delivery. In particular, nutrient starvation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 51 publications
2
69
0
Order By: Relevance
“…As reported in Figure 3(a), ATGL lacking cells [ATGL(−)] displayed impaired PPAR α expression and higher expression of TNF α and IL-6 than controls, in line with what we observed in C 2 C 12 myotubes (Figure 2(b)) and previously revealed on primary adipocytes and mouse embryonic fibroblasts [5]. However, contrary to what we observed in 21-day-old adipocytes, RSV was unable to revert the induction of TNF α and IL-6 in ATGL(−) adipocytes; but rather it unexpectedly further upregulated their mRNA expression, indicating an enhancement of NF κ B activity (Figure 3(a)).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As reported in Figure 3(a), ATGL lacking cells [ATGL(−)] displayed impaired PPAR α expression and higher expression of TNF α and IL-6 than controls, in line with what we observed in C 2 C 12 myotubes (Figure 2(b)) and previously revealed on primary adipocytes and mouse embryonic fibroblasts [5]. However, contrary to what we observed in 21-day-old adipocytes, RSV was unable to revert the induction of TNF α and IL-6 in ATGL(−) adipocytes; but rather it unexpectedly further upregulated their mRNA expression, indicating an enhancement of NF κ B activity (Figure 3(a)).…”
Section: Resultssupporting
confidence: 90%
“…Therefore, on the basis of these data we can postulate that the failure of ATGL-mediated stress response observed in 24-month-old and 21-day-old adipocytes triggers the production of proinflammatory cytokines. In agreement with this idea, higher levels of inflammatory markers were observed upon ATGL downregulation in vitro and in vAT of ATGL KO mice [5]. The modulatory action of ATGL on tissue inflammation has been reported recently also in cardiac muscle [15].…”
Section: Resultsmentioning
confidence: 53%
“…As concerns the activation of FoxO1 in starved adipocytes, the mitochondrial ROS were identified as the triggering molecules. More specifically, activation of the proline oxidase/dehydrogenase (POX/PRODH), a mitochondrial inner-membrane enzyme that starts proline catabolism, contributes to generate ROS under nutrient shortage [89]. In support of the relevance of ROS signaling in FoxO1 nuclear translocation in adipocytes and lipolysis activation were the results with the antioxidant N-acetylcysteine, which abrogated both phenomena [27,90].…”
Section: Foxo1 Response To Ros In Adipocytesmentioning
confidence: 94%
“…ATGL activity is normally inhibited by insulin [154] and it has been suggested that insulin resistance that develops with chronic ethanol abuse could mechanistically be related to increased WAT lipolysis [152]. Further ethanol-induced oxidative stress [155, 156] can also induce ATGL expression in a FoxO1-dependent manner [157]. …”
Section: Changes In Adipocyte Lds After Ethanol Administrationmentioning
confidence: 99%